2016
DOI: 10.1088/0957-4484/27/48/485603
|View full text |Cite
|
Sign up to set email alerts
|

Nanoring formation viain situphotoreduction of silver on a virus scaffold

Abstract: The fabrication of plasmonic nanorings remains of substantial interest by virtue of their enhanced electric and magnetic response to light fields which can be subsequently exploited in diverse applications. Scaling down the size of nanorings holds promise in creating artificial magnetism at wavelengths matching the solar spectrum. Nanosized bioscaffolds can be utilized to tackle the challenge of size reduction of metallic rings owing to their miniature features as well as their well-known biomineralization cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…It is worth mentioning here that several examples of metallic nanorings synthesis and fabrication have been reported in literature . In almost all the cases the size of the rings, in terms of outer and inner diameters, is in the scale of tens of nanometers, that is, an order of magnitude larger than the structures obtained here. Micrographs clearly show that the nanorings exhibit an apparent rough surface suggesting that metal seeding growth might have occurred during the synthesis.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…It is worth mentioning here that several examples of metallic nanorings synthesis and fabrication have been reported in literature . In almost all the cases the size of the rings, in terms of outer and inner diameters, is in the scale of tens of nanometers, that is, an order of magnitude larger than the structures obtained here. Micrographs clearly show that the nanorings exhibit an apparent rough surface suggesting that metal seeding growth might have occurred during the synthesis.…”
Section: Resultsmentioning
confidence: 64%
“…In particular, DNA and proteins are considered groundbreaking tools as they naturally self‐assemble into several multi‐level architectures . Proteins are being explored for supramolecular chemistry applications and inspire the design of novel artificial nanomaterials fabricated by biotechnological, chemical, and computational expedients . The access to ready‐to‐use protein assemblies with discrete structural patterns such as cages, rings, and tubes is leading to promising results, for example, in magnetic resonance‐based imaging .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, plasmonic nanorings with magnetic and electric field resonances at visible frequencies can be templated by TMV's disk‐like conformation. In 2016, Bayram, Zahr, Del Re, and Blum () have shown that the formation of silver NPs (AgNPs) can be mediated by carboxyl groups on the wt‐TMV disk under UV illumination at neutral conditions without the need for a chemical reductant. The mutation of a surface‐exposed serine to a cysteine (S123C‐TMV) afforded additional binding sites for silver, thus triggering the formation of continuous silver toroids following photoreduction.…”
Section: Introductionmentioning
confidence: 99%
“…Although sonification or etching was used to peel nanorings from substrates, the peeling procedure often damaged the ring structure. Therefore, scientists attempted to use separate templates [14] to prepare monodisperse rings, but the ring shapes were not well-defined except for those obtained by the coaxial lithography involving block copolymer-like nanowires as templates. [14d,e] Since scalable nanoparticles with varied morphologies are widely available, directly transforming individual preformed nanoparticles into nanorings may be a more flexible way for fabricating free-standing nanorings by employing chemical oxidation [15] or galvanic replacement, [16] which, however, was demonstrated just for plate/sheet-like nanoparticles.…”
Section: Introductionmentioning
confidence: 99%